Consolidation therapy with the combination of bortezomib and lenalidomide (VR) without dexamethasone in multiple myeloma patients after transplant: Effects on survival and bone outcomes in the absence of bisphosphonates. Issue 4 (10th January 2019) - Terpos, Evangelos; Kastritis, Efstathios; Ntanasis‐Stathopoulos, Ioannis; Christoulas, Dimitrios; Papatheodorou, Athanasios; Eleutherakis‐Papaiakovou, Evangelos; Kanellias, Nikolaos; Fotiou, Despina; Ziogas, Dimitrios C.; Migkou, Magdalini; Roussou, Maria; Trougakos, Ioannis P.; et al.
Abstract : Optimizing consolidation treatment in transplant‐eligible newly diagnosed multiple myeloma patients in order to improve efficacy and bone‐related outcomes is intriguing. We conducted an open‐label, prospective study evaluating the efficacy and safety of bortezomib and lenalidomide (VR) consolidation after ASCT, in the absence of dexamethasone and bisphosphonates. Fifty‐nine patients, who received bortezomib‐based induction, were given 4 cycles of VR starting on day 100 post‐ASCT. After ASCT, 58% of patients improved their response status, while following VR consolidation 39% further deepened their response; stringent complete response rates increased to 51% after VR from 24% post‐ASCT. VR consolidation resulted in a significant reduction of soluble receptor activator of nuclear factor‐κB ligand/osteoprotegerin ratio and sclerostin circulating levels, which was more pronounced among patients achieving very good partial response or better. After a median follow‐up of 62 months, no skeletal‐related events (SREs) were observed, despite the lack of bisphosphonates administration. The median TTP after ASCT was 37 months, while median overall survival (OS) has not been reached yet; the probability of 4‐ and 5‐year OS was 81% and 64%, respectively. In conclusion, VR consolidation is an effective, dexamethasone‐ and bisphosphonate‐free approach, which offers long OS with improvements on bone metabolism and no SREs.